The Effectiveness of Problem-Posing Learning Model in Terms of Creative Thinking Skills and Math Anxiety - Wulandari, Ayuning Tyas; Abadi, Agus Maman; Radite, Ramadian (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to analyze the effectiveness of problem-posing in terms of creative thinking ability and math anxiety simultaneously as well as analyze the difference in effectiveness between problem-posing and scientific in terms of creative thinking ability and math anxiety simultaneously. Quantitative research type quasi-experimental with a posttest-only control group design was conducted on grade X students at one of the State Senior High Schools in Wonogiri Regency, Central Java Province, Indonesia. The research samples were selected randomly from 11 classes and obtained two classes X1 and X3, each with 36 students. Data on creative thinking were obtained through essay tests, which included fluency, flexibility, and novelty aspects. Math anxiety data were obtained through a Likert-scale questionnaire with psychological, cognitive, affective, and attitude aspects. The study results showed that problem-posing was simultaneously effective in creative thinking and math anxiety. However, there was no difference in effectiveness between problem-posing and scientific in students' creative thinking and math anxiety. Following this result, there are research opportunities regarding analyzing the relationship between the level of math anxiety and creative thinking in solving problems based on higher-order thinking skills.